Optimalisasi Industri Rumah Tangga Dapur Mindul Melalui Inovasi Kemasan dan Label - Rizki, Via Lailatur (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
Fast-growing business for small entrepreneurs such as the household industry must always innovate to boost their ventures. Innovation is done not only through the product, but also through the attractive packaging and labelling of the processed product to give the brand image of the enterprise. This dedication to the Society aims to optimize the household industry of Dapur Mindul through innovation of packaging and labels. This method of dedication is material explanation, discussion, and and labeling training through canva. This dedication activity is carried out with observation, identification of problems, implementation of activities and evaluation. The result of this activity is an increased understanding of the Dapur Mindul household industry regarding the importance of packaging innovation and labels, as well as the use of canva for label design. The outward result of these activities is an attractive packaging adapted to the processing of products, and the mindul kitchen business label to give a brand image or business identity.